Is peer delinquency in the eye of the beholder?: assessing alternative operationalizations of perceptual peer delinquency - Meldrum, Ryan Charles (Criminal justice and behavior, 2015)
Researchers have devoted significant attention to the measurement of peer delinquency, with recent work indicating that perceptual measures are plagued by various biases. Absent from this research is an inquiry into whether the manner in which perceptions are typically operationalized potentially contributes to these limitations. In this study, we report on a methodological quasi-experiment where the operationalization of perceptual peer delinquency was manipulated across two different versions of a survey questionnaire completed by a sample of young adults. Results indicated no significant difference in the strength of the association between perceptual peer delinquency items and self-reported delinquency items across the two survey conditions. As such, this study provides preliminary evidence that existing limitations of perceptual measures of peer delinquency cannot be overcome by altering the manner in which such items are operationalized within survey questionnaires.